2016
DOI: 10.3109/15376516.2015.1122136
|View full text |Cite
|
Sign up to set email alerts
|

Hearing, reactive metabolite formation, and oxidative stress in cochleae after a single acute overdose of acetaminophen: anin vivostudy

Abstract: Context Although the liver is the primary target organ in acetaminophen (APAP) toxicity, other organs are affected. Previous data suggested chronic APAP abuse can be ototoxic and the mechanism involves APAP-induced oxidative stress and reactive metabolite (NAPQI)-induced endoplasmic reticulum stress. However, the effect of a single acute overdose on hearing has not been tested. Objectives To determine if a single acute APAP overdose causes hearing damage, and to explore possible mechanisms of APAP ototoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Furthermore, the same group published a more recent study indicating that APAP does not actually cause cell death in HEIOC1 cells, despite evidence of reduced energy metabolism and even increased caspase activity [162]. Finally, a recent in vivo study in mice found no evidence for hearing loss based on auditory brainstem response (ABR) in a clinically relevant model of acute APAP overdose [163]. Thus, it seems unlikely that APAP by itself causes ototoxicity in humans or mice.…”
Section: Ototoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the same group published a more recent study indicating that APAP does not actually cause cell death in HEIOC1 cells, despite evidence of reduced energy metabolism and even increased caspase activity [162]. Finally, a recent in vivo study in mice found no evidence for hearing loss based on auditory brainstem response (ABR) in a clinically relevant model of acute APAP overdose [163]. Thus, it seems unlikely that APAP by itself causes ototoxicity in humans or mice.…”
Section: Ototoxicitymentioning
confidence: 99%
“…Based on these findings, the authors concluded that APAP and NAPQI exert toxic effects through different mechanisms in cochlear cells: APAP ototoxicity involves oxidative stress and ER stress, while NAPQI causes ER stress without oxidative stress [13]. The only in vivo study of APAP ototoxicity to date also revealed that there is oxidative stress in cochleae after acute APAP overdose [163]; however, no ototoxicity was observed in that study based on auditory brainstem thresholds (ABR) [163].…”
Section: Ototoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study suggested that guavas can inhibit caspase activity to attenuate cell apoptosis in type II diabetic rats (32). Because APAP-induced cytotoxicity is related to oxidative stress and caspase activity (13)(14)(15)(16)33,34), and because guavas can inhibit oxidative stress and caspase activity, the present study investigated whether guavas can attenuate APAP-induced renal cytotoxicity.…”
Section: Introductionmentioning
confidence: 94%
“…Many studies have shown that high doses of APAP can induce cell death through either the apoptotic or necrotic death pathways (10)(11)(12). Previous studies have demonstrated that APAP-induced cytotoxicity is related to increased oxidative stress and glutathione depletion (13)(14)(15)(16). It is well-known that cellular glutathione can convert H 2 O 2 to H 2 O via a glutathione peroxidase reaction to attenuate cellular oxidative stress (17,18).…”
Section: Introductionmentioning
confidence: 99%